English-Malay-English Dictionary - Norafidah, Md Yusof (2012)
English-Malay-English Dictionary is a solution to the problems that always occur to the tourist from abroad when they come to Malaysia.This thesis was about what had done in order to try to solve the problem by develop the English-Malay-English Dictionary in mobile.The English-Malay-English Dictionary was develop in mobile because nowadays mobile is an important gadget for everyone.This is because mobile is easy to carry with its size which is small and the price that suitable for everyone. The dictionary is choosing for the case study since there are many tourists got problems to communicate with the Malaysian.From the research, they are having done the dictionary in mobile that had cover two language which are Mandarin and English language that caused the dictionary is Mandarin-English dictionary.That is means English-Malay-English Dictionary is a new application that can attract tourist to come to Malaysia because they can understand and communicate with the Malaysian by using this dictionary. The English-Malay-English Dictionary is developing to make the newest dictionary for Android Smartphone. By having this dictionary, tourists no need to worry about the communication problem with Malaysian.